ANALISIS ELABORATION LIKELIHOOD MODEL DALAM PEMBENTUKAN PERSONAL BRANDING DI TWITTER - Tuti Widiastuti Widiastuti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2017)
This study sought to look at the fact that twitter can shape one’s personal branding, then on the basis of this research is compiled on how the analysis elaboration likelihood model in the formation of personal branding in social media. The method used in this research is quantitative content analysis method. The study population was the whole text or tweets made by Ridwan Kamil through his twitter account (@ridwankamil). This study shows, twitter contents can shape one’s personal branding. Establishment of personal branding can be done through posts made in his twitter. The formation of personal branding is seen from the theme of writing, retweet and favorite number, type of writing, the uniqueness of writing and writing direction. Establishment of personal branding is required by a person not only through the writings conveyed through the media, but also the need for real action participation and involvement in community life.